Divergent Roles of Central Serotonin in Adult Hippocampal Neurogenesis - Song, Ning-Ning; Huang, Ying; Yu, Xin; Lang, Bing; Ding, Yu-Qiang; Zhang, Lei (Frontiers in Cellular Neuroscience, 2017)
The central serotonin (5-HT) system is the main target of selective serotonin reuptake inhibitors (SSRIs), the first-line antidepressants widely used in current general practice. One of the prominent features of chronic SSRI treatment in rodents is the enhanced adult neurogenesis in the hippocampus, which has been proposed to contribute to antidepressant effects. Therefore, tremendous effort has been made to decipher how central 5-HT regulates adult hippocampal neurogenesis. In this paper, we review how changes in the central serotonergic system alter adult neurogenesis. We focus on data obtained from three categories of genetically engineered mouse models: (1) mice with altered central 5-HT levels from embryonic stages, (2) mice with deletion of 5-HT receptors from embryonic stages, and (3) mice with altered central 5-HT system exclusively in adulthood. These recent findings provide unique insights to interpret the multifaceted roles of central 5-HT on adult hippocampal neurogenesis and its associated effects on depression.